Patients with peripheral artery disease demonstrate altered expression of soluble and membrane-bound immune checkpoints - Rosanne D. Reitsema; Seta Kurt; Seta Kurt; Ignacio Rangel; Hans Hjelmqvist; Hans Hjelmqvist; Mats Dreifaldt; Allan Sirsjö; Ashok Kumar Kumawat (Frontiers in Immunology)
IntroductionStudies suggest that immune checkpoints play a role in accelerating the formation of atherosclerosis. We aimed to assess the expression of soluble and membrane-bound immune checkpoints in patients with peripheral artery disease (PAD).MethodsThe levels of 14 soluble immune checkpoints were assessed in blood plasma of PAD patients (n= 37) and healthy controls (HCs, n=39) by Multiplex protein assay. The surface expression of immune checkpoints on peripheral blood immune cells was determined by flow cytometry. Cytokine production capacity was measured by flow cytometry in TIM-3+ T cells to determine immune exhaustion.ResultsSoluble levels of PD-L2 were decreased in female PAD patients, whereas soluble levels of TIM-3 showed a trend towards an increased concentration in female PAD patients. PD-L2+ frequencies were higher within all monocyte subsets in PAD patients. CD4+ T cells from PAD patients had increased frequencies of TIM-3+ cells, showing little overlap with other immune exhaustion markers. TIM-3+ CD4+ T cells from both PAD patients and HCs, had a low capacity to produce pro-inflammatory cytokines, but a higher capacity to produce IL-10 compared to TIM-3- CD4+ T cells.ConclusionPAD patients show differences in the expression of membrane-bound and soluble immune checkpoints. Some of these differences might be caused by prolonged immune activation, although immune exhaustion markers did not always overlap.